Be Healthy in Pregnancy: Exploring factors that impact pregnant women's nutrition and exercise behaviours. Issue 1 (23rd July 2020) - Grenier, Lindsay N.; Atkinson, Stephanie A.; Mottola, Michelle F.; Wahoush, Olive; Thabane, Lehana; Xie, Feng; Vickers‐Manzin, Jennifer; Moore, Caroline; Hutton, Eileen K.; Murray‐Davis, Beth
Abstract: Excess gestational weight gain is associated with short‐ and long‐term pregnancy complications. Although a healthy diet and physical activity during pregnancy are recommended and shown to reduce the risk of complications and improve outcomes, adherence to these recommendations is low. The aims of this study were to explore women's view of nutrition and physical activity during pregnancy and to describe barriers and facilitators experienced in implementing physical activity and nutrition recommendations. In a substudy of the Be Healthy in Pregnancy randomized trial, 20 semistructured focus groups were conducted with 66 women randomized to the control group when they were between 16 and 24 weeks gestation. Focus groups were recorded, transcribed verbatim, coded and thematically analysed. The results indicate that women felt motivated to be healthy for their baby, but competing priorities may take precedence. Participants described limited knowledge and access to information on safe physical activity in pregnancy and lacked the skills needed to operationalize both physical activity and dietary recommendations. Women's behaviours regarding diet and physical activity in pregnancy were highly influenced by their own and their peers' beliefs and values regarding how weight gain impacted their health during pregnancy. Pregnancy symptoms beyond women's control such as fatigue and nausea made physical activity and healthy eating more challenging. Counselling from care providers about nutrition and physical activity was perceived as minimal and ineffective. Future interventions should address improving counselling strategies and address individual's beliefs around nutrition and activity in pregnancy.